OP0222 (Collagen Specific-)T Cell Related Parameters Provide Information for the Management of Rheumatoid Arthritis Patients. (10th June 2014) - Di Sante, G.; Nicolò, C.; Fedele, A.L.; Gremese, E.; Tolusso, B.; Carbonella, A.; Gigante, M.R.; Bosello, S.L.; Ria, F.; Ferraccioli, G.
Abstract : Background: The developmental risk of Rheumatoid Arthritis (RA) is strongly linked to HLA-DRB1*04 (DR4) and *01 (DR1). In RA, activated immune cells, as CD4+T cells, B cells, dendritic cells and macrophages infiltrate the synovial tissue. In a previous work, we found that huCollp261-273-specific T cell repertoire analyzed in peripheral blood of DR4+ RA patients was restricted to a limited number of TCR rearrangements. This collagen-specific repertoire appears modulated by disease activity (1). The two most used TCR-beta chains were TRBV25-TRBJ2.2 and TRBV6-4-TRBJ2-3. Objectives: To examine the frequency and the distribution of huCollp261-273-specific T cells and the role of DR alleles in RA patients in order to find new biomarker for the management of the disease. Methods: HLA genotyping was performed using the Innogenetics® kit, following the manufacturer's protocol. TCR repertoire analysis: Peripheral blood mononuclear cells (PBMCs) were purified from whole blood and TCR BV-JB analysis was performed as previously described. (1) Patients: we analyzed 100 samples from RA patients, 57 with a high disease activity (DAS >3.7) and 43 with a low disease activity (DAS≤2.4). Results: The presence of TRBV25-TRBJ2.2 and TRBV6-4-TRBJ2-3 in T cells was significantly associated with disease activity in the group of DR4+ RA patients. The usage of these two receptors described two non-overlapping groups of RA patients, with subjects using TRBV6-4+ displaying a significantly higher disease activity. The combination of TCR usage in DR4+ subjects and of DR haplotypes in RA patients described four distinct responses to treatment with Disease Modifying Antirheumatic Drugs (DMARDs) and biologic agents. Fifty percent of DR4+ TRBV25- patients responded to DMARDs and the remaining responded well to biologic agents; DR4+ TRBV25+ patients failed to respond to DMARDs but displayed a good response to biologic agents and this latter group might therefore be candidate to treatment with biologic agents. In the group of DR4-, DR1- or DR7-patients, the DR11 allele appeared highly enriched in subjects displaying a high disease activity. Accordingly, within the group of DR4-, DR1- DR7- RA patients, we observed that 50% of all patients achieved a good response after DMARDs treatment; among patients non-responder to DMARDs, however, it appeared that DR11+ subjects responded to a lesser extent than DR11- patients to biologic agents. Conclusions: These findings showed that the analysis of collagen specific T cells repertoire and HLA-DR haplotype can provide useful information to a personalized treatment in RA patients. References: Ria F., et al. Arthritis Research & Therapy, 2008. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4311